Yarn texturing technology - Hearle, J. W. S. (CRC Press ; Woodhead Pub., 2001)
This book covers all the major techniques including twist texturing, jet-screen texturing, false-twist process, BCF processes and air-jet texturing in detail. It will be invaluable for yarn and fabric manufacturers, textile scientists and students on textile science and technology courses.
Keywords: Textured yarn.; elektronické knihy; electronic books